2013
DOI: 10.1136/bjsports-2013-092386
|View full text |Cite
|
Sign up to set email alerts
|

Realising the potential for an Olympic legacy; teaching medical students about sport and exercise medicine and exercise prescribing

Abstract: Behaviour change teaching successfully improved students' knowledge of and confidence regarding PA promotion. These improvements are a step forward and may increase the rates and success of physician PA counselling in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 22 publications
2
28
1
Order By: Relevance
“…Green Prescription Initiative in New Zealand), understanding of specific benefits of exercise such as the safety of exercise in clinical populations and the awareness of the other health professionals who can assist in providing further PA advice. These findings are consistent with the results of recent studies and findings from a recent systematic review on PA counselling in medical school education (Dacey et al, 2014;Jones, Brooks & Wylie, 2013). The authors of the present study previously reported that New Zealand medical students had a good understanding of the links between exercise and health and positive attitudes towards PA advising in general practice (Mandic et al, 2017) and those outcomes were not changed considerably after the intervention in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Green Prescription Initiative in New Zealand), understanding of specific benefits of exercise such as the safety of exercise in clinical populations and the awareness of the other health professionals who can assist in providing further PA advice. These findings are consistent with the results of recent studies and findings from a recent systematic review on PA counselling in medical school education (Dacey et al, 2014;Jones, Brooks & Wylie, 2013). The authors of the present study previously reported that New Zealand medical students had a good understanding of the links between exercise and health and positive attitudes towards PA advising in general practice (Mandic et al, 2017) and those outcomes were not changed considerably after the intervention in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, more extensive training in PA advising may be necessary as a part of the undergraduate medical curriculum to develop medical students' skills, knowledge and confidence for providing effective PA advice in future. As suggested previously, improving medical students' knowledge of and confidence regarding PA promotion is a step forward and may increase the rates and effectiveness of physicians' PA counselling in the future (Jones et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Articles that were excluded were: (a) not written in English; (b) review articles; and (c) written before 2010, as this was prior to the publication of the WHO guidelines. (10) For the survey of students, a 12-item anonymised Google Forms survey was constructed based on previous studies, (22,23,25,26) consisting of two parts (Box 1). The first section collected demographic information about the participants, including the medical school that they were based at and their year of study.…”
Section: Methodsmentioning
confidence: 99%
“…(21) Therefore, training medical professionals is an essential component of the broader strategy in PA promotion. This problem, however, appears to stem from an early stage in a doctor's training -several studies highlight the paucity of sports and exercise medicine teaching in the official curriculum, (22,23) as well as limited knowledge about PA and its role in health among medical students. (24) In line with the current challenges of PA promotion in healthcare and the lack of information regarding the level of sports and exercise medicine training at medical schools, it is necessary to establish how much teaching in undergraduate curricula focuses on PA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in South Africa, more than 50% of private medical insurance members have more than one chronic disease and some have up to 11 simultaneous chronic conditions 13. Thus, new models of prevention are urgently required and should be included in the undergraduate medical curriculum 14. This new model should be comprehensive, health-based, patient-centred and integrated for clinically effective and cost-effective prevention and management of chronic diseases 15…”
Section: Introductionmentioning
confidence: 99%